The function and mechanism of protein acylation in the regulation of viral infection - Lei Song; Ziang Wei; Pan Shang; Shijie Hu; Lei Chen; Lili Niu; Yan Wang; Mailin Gan; Linyuan Shen; Li Zhu; Ye Zhao (Virulence, 2025)
Protein acylation modification is one of the most important protein post-translational modifications, which regulates the function of the protein by adding acyl groups to the residues of the protein. Protein acylation plays a crucial role in viral infection. Acylation can influence viral proteins, thereby regulating processes such as viral entry, replication, and assembly. Additionally, acylation regulates viral infection by regulating interferon pathway, cell metabolism, and signal transduction. This paper mainly elucidates the mechanism of acetylation, succinylation, and palmitoylation in the regulation of viral infection.